L'engagement en doctorat des formateurs aux métiers du care - Céline Mahieu
More and more teachers of higher education are entering doctoral studies. This seems to be related to the process of universitarisation. Are there other reasons? How do they manage to stay involved when they are returning to study and have to reconcile their training with their other life trajectories? This article focuses on the specific case of midwifery teachers. We conducted longitudinal qualitative research with interviews of 15 midwifery teachers who were in the process of completing their doctorate at one year intervals. The results show that they see their commitment as an investment in their profession and in the science of midwifery. Despite the difficulties they face, they show stamina. We identify factors influencing their continued commitment and mental health, such as recognition of doctoral work by others and a supportive relationship with their supervisor(s).